Hot Integral - 7

Calculus Level 5

I n ( x ) = 2 n + 1 π e x 2 0 t n cos ( 2 x t n π 2 ) e t 2 d t \qquad \quad \displaystyle I_n(x) = \frac{2^{n+1}}{\sqrt{\pi}}e^{x^2}\int\limits_0^{\infty}\frac{t^n \cos(2xt - \frac{n \pi}{2})}{e^{t^2}} dt

Then , the following integral :

e ( 1 t ) 2 I 2 ( t ) d t = k \displaystyle \int\limits_{-\infty}^{\infty}e^{-(1-t)^2}I_2(t) dt = k

Calculate k \lfloor k \rfloor .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Hasan Kassim
Aug 9, 2015

I solved it using the Gaussian Integral .

First find the closed form of I 2 ( x ) I_2(x) :

I 2 ( x ) = 8 e x 2 π 0 t 2 cos ( 2 x t ) e t 2 d t \displaystyle I_2(x) =- \frac{8e^{x^2}}{\sqrt{\pi}} \int_0^{\infty} t^2\cos (2xt) e^{-t^2} dt

= 4 e x 2 π t 2 cos ( 2 x t ) e t 2 d t \displaystyle = -\frac{4e^{x^2}}{\sqrt{\pi}} \int_{-\infty}^{\infty} t^2\cos (2xt) e^{-t^2} dt

= 4 e x 2 π t 2 e 2 x t i e t 2 d t \displaystyle =- \Re \frac{4e^{x^2}}{\sqrt{\pi}} \int_{-\infty}^{\infty} t^2 e^{2xti} e^{-t^2} dt

= 4 e x 2 π t 2 e 2 x t i e t 2 d t \displaystyle =- \Re \frac{4e^{x^2}}{\sqrt{\pi}} \int_{-\infty}^{\infty} t^2 e^{2xti} e^{-t^2} dt

= 4 π t 2 e x 2 e 2 x t i e t 2 d t \displaystyle = -\Re \frac{4}{\sqrt{\pi}} \int_{-\infty}^{\infty} t^2 e^{x^2} e^{2xti} e^{-t^2} dt

= 4 π t 2 e ( t i x ) 2 d t \displaystyle =- \Re \frac{4}{\sqrt{\pi}} \int_{-\infty}^{\infty} t^2 e^{-(t-ix)^2} dt

= t ( t + i x ) 4 π ( t + i x ) 2 e t 2 d t \displaystyle \overset{{\color{grey}{t \to (t+ix) }}}{=} -\Re \frac{4}{\sqrt{\pi}} \int_{-\infty}^{\infty} (t+ix)^2 e^{-t^2} dt

= 4 π ( t 2 e t 2 d t + 2 i x t e t 2 d t + ( i x ) 2 e t 2 d t ) \displaystyle = - \Re \frac{4}{\sqrt{\pi}} \bigg( {\color{#3D99F6}{\int_{-\infty}^{\infty} t^2 e^{-t^2} dt }}+ 2ix {\color{#D61F06}{\int_{-\infty}^{\infty} t e^{-t^2} dt }}+ (ix)^2 {\color{#20A900}{\int_{-\infty}^{\infty} e^{-t^2} dt}} \bigg)

-The Blue {\color{#3D99F6}{\text{Blue}}} Integral:

Use Integration by parts with u = t , d v = t e t 2 d t u= t \; , \; dv = te^{-t^2} dt :

= ( t ) ( 1 2 e t 2 ) + 1 2 e t 2 d t \displaystyle = (t)(-\frac{1}{2}e^{-t^2} ) |_{-\infty}^{\infty} +\frac{1}{2} \int_{-\infty}^{\infty} e^{-t^2} dt

= π 2 \displaystyle = {\color{#3D99F6}{\frac{\sqrt{\pi}}{2} }}

-The Red {\color{#D61F06}{\text{Red}}} Integral :

I will check its absolute convergence :

t e t 2 d t = 2 0 t e t 2 d t \displaystyle \int_{-\infty}^{\infty} |t e^{-t^2} |dt = 2\int_0^{\infty} te^{-t^2} dt

= t t 0 e t d t = 1 \displaystyle \overset{{\color{grey}{t \to \sqrt{t} }}}{=} \int_0^{\infty} e^{-t} dt =1

And hence it is absolutely convergent.

We have an odd function and opposite integration limits :

= 0 \displaystyle ={\color{#D61F06}{0}}

-The Green {\color{#20A900}{\text{Green}}} Integral:

It is Simply the Gaussian Integral:

= π \displaystyle = {\color{#20A900}{\sqrt{\pi}}}

Hence:

I 2 ( x ) = 4 π ( π 2 + 2 i x ( 0 ) + ( i x ) 2 π ) = 4 x 2 2 \displaystyle I_2(x) = - \Re \frac{4}{\sqrt{\pi}} \bigg( {\color{#3D99F6}{\frac{\sqrt{\pi}}{2} }} + 2ix({\color{#D61F06}{0}} )+ (ix)^2 {\color{#20A900}{\sqrt{\pi}}} \bigg) = 4x^2 -2

Now solve the desired integral:

k = e ( t 1 ) 2 I 2 ( t ) d t = ( 4 t 2 2 ) e ( t 1 ) 2 d t \displaystyle k= \int_{-\infty}^{\infty} e^{-(t-1)^2} I_2(t) dt = \int_{-\infty}^{\infty} (4t^2-2) e^{-(t-1)^2} dt

= t ( t + 1 ) ( 4 t 2 + 8 t + 2 ) e t 2 d t \displaystyle \overset{{\color{grey}{t \to (t+1) }}}{=} \int_{-\infty}^{\infty} (4t^2+8t +2) e^{-t^2} dt

= 4 t 2 e t 2 d t + 8 t e t 2 d t + 2 e t 2 d t \displaystyle = 4 {\color{#3D99F6}{\int_{-\infty}^{\infty} t^2 e^{-t^2} dt }}+ 8 {\color{#D61F06}{\int_{-\infty}^{\infty} t e^{-t^2} dt }}+ 2 {\color{#20A900}{\int_{-\infty}^{\infty} e^{-t^2} dt}}

These integrals were solved above, hence we have:

k = 4 ( π 2 ) + 8 ( 0 ) + 2 ( π ) = 4 π \displaystyle k= 4({\color{#3D99F6}{\frac{\sqrt{\pi}}{2} }}) +8({\color{#D61F06}{0}}) + 2 ({\color{#20A900}{\sqrt{\pi}}} ) = 4\sqrt{\pi}

= > k = 4 π = 7.08982 = 7 => \lfloor k \rfloor = \lfloor 4\sqrt{\pi} \rfloor = \lfloor 7.08982 \rfloor = \boxed{7}

Moderator note:

Note that you have to check that the red integral is absolutely convergent, before you can conclude that it is not undefined, and hence equal to 0. E.g. \int_{-\infty}^{\infty} \frac{1}[x} \, dx is undefined.

Loved it dude

solution is more hotter :D

Aman Rajput - 5 years, 10 months ago

Challenge Master: Edited!

Hasan Kassim - 5 years, 10 months ago

Mine involved Mellin transform, Gamma function and much more fancier names than yours. Great solution! Should I post mine? I don't think so after yours.

Kartik Sharma - 5 years, 10 months ago

Log in to reply

It's great to learn other approaches , post your solution :)

Hasan Kassim - 5 years, 10 months ago

you should post yours... my vote is ready .. and waiting for that

Aman Rajput - 5 years, 10 months ago

Log in to reply

Yes and my vote also !

And Aman, don't you have an approach involving the Hermite polynomials? Post it please I don't know anything about them..

Hasan Kassim - 5 years, 10 months ago
Mark Hennings
Jan 11, 2016

The defining integral for I n I_n is a standard one! We have I n ( x ) = H n ( x ) I_n(x) = H_n(x) , the n n th Hermite polynomial. It is easy to show that the generating function of the I n I_n is n = 0 I n ( x ) t n n ! = e 2 x t t 2 , \sum_{n=0}^\infty I_n(x) \frac{t^n}{n!} \; =\; e^{2xt - t^2} \;, which is the same as the generating function of the Hermite polynomials.

The desired integral is thus R e ( t 1 ) 2 H 2 ( t ) d t = R e t 2 H 2 ( t + 1 ) d t = R e t 2 ( 4 ( t + 1 ) 2 2 ) d t = R e t 2 ( H 2 ( t ) + 4 H 1 ( t ) + 4 H 0 ( t ) ) d t = R e t 2 ( H 2 ( t ) + 4 H 1 ( t ) + 4 H 0 ( t ) ) H 0 ( t ) d t = 4 R e t 2 H 0 ( t ) 2 d t = 4 π \begin{array}{rcl} \displaystyle\int_{\mathbb{R}} e^{-(t-1)^2} H_2(t)\,dt & = & \displaystyle\int_{\mathbb{R}} e^{-t^2}H_2(t+1)\,dt \; = \; \int_{\mathbb{R}} e^{-t^2} \big(4(t+1)^2 - 2\big)\,dt \\ & = &\displaystyle \int_{\mathbb{R}} e^{-t^2}\big(H_2(t) + 4H_1(t) + 4H_0(t)\big)\,dt \\ & = & \displaystyle \int_{\mathbb{R}} e^{-t^2}\big(H_2(t) + 4H_1(t) + 4H_0(t)\big)H_0(t)\,dt \\ & = & \displaystyle4\int_{\mathbb{R}} e^{-t^2} H_0(t)^2\,dt \; = \; 4\sqrt{\pi} \end{array} using the orthogonality properties of the Hermite polynomials.

Nice .. :)

Aman Rajput - 5 years, 5 months ago
Kartik Sharma
Aug 13, 2015

I 2 ( x ) = 8 e x 2 π 0 t 2 c o s ( 2 x t ) e t 2 d t \displaystyle {I}_{2}(x) = - \frac{8{e}^{{x}^{2}}}{\sqrt{\pi}} \int\limits_{0}^{\infty}{{t}^{2}cos(2xt){e}^{-{t}^{2}} dt}

I 2 ( x ) = 8 e x 2 π 0 t 2 e t 2 k = 0 ( 1 ) k ( 2 x t ) 2 k ( 2 k ) ! d t \displaystyle {I}_{2}(x) = - \frac{8{e}^{{x}^{2}}}{\sqrt{\pi}} \int\limits_{0}^{\infty}{{t}^{2}{e}^{-{t}^{2}} \sum_{k=0}^{\infty}{\frac{{(-1)}^{k}{(2xt)}^{2k}}{(2k)!}} dt}

I 2 ( x ) = 8 e x 2 π k = 0 ( 1 ) k ( 2 x ) 2 k ( 2 k ) ! 0 t 2 + 2 k e t 2 d t \displaystyle {I}_{2}(x) = - \frac{8{e}^{{x}^{2}}}{\sqrt{\pi}} \sum_{k=0}^{\infty}{\frac{{(-1)}^{k}{(2x)}^{2k}}{(2k)!} \int\limits_{0}^{\infty}{{t}^{2+2k}{e}^{-{t}^{2}} dt}}

Using U-substitution and Gamma function's definition, we can write it as -

I 2 ( x ) = 8 e x 2 π k = 0 ( 1 ) k ( 2 x ) 2 k ( 2 k ) ! Γ ( k + 1 + 1 2 ) \displaystyle {I}_{2}(x) = - \frac{8{e}^{{x}^{2}}}{\sqrt{\pi}} \sum_{k=0}^{\infty}{\frac{{(-1)}^{k}{(2x)}^{2k}}{(2k)!}\Gamma\left(k+1+\frac{1}{2}\right)}

Using Gamma function property,

= 8 e x 2 π k = 0 ( 1 ) k ( 2 x ) 2 k ( 2 k ) ! ( 2 k + 2 ) ! π 2 2 k + 2 ( k + 1 ) ! \displaystyle = - \frac{8{e}^{{x}^{2}}}{\sqrt{\pi}} \sum_{k=0}^{\infty}{\frac{{(-1)}^{k}{(2x)}^{2k}}{(2k)!}\frac{(2k+2)!\sqrt{\pi}}{{2}^{2k+2}(k+1)!}}

Simplifying,

= 2 e x 2 k = 0 ( x 2 ) k ( 2 k + 1 ) k ! \displaystyle = - 2{e}^{{x}^{2}} \sum_{k=0}^{\infty}{\frac{{(-{x}^{2})}^{k}(2k+1)}{k!}}

Using the Taylor series of e x {e}^{x} and then differentiation, one can get

= 2 e x 2 ( e x 2 ( 2 x 2 1 ) ) \displaystyle = -2{e}^{{x}^{2}}\left(-{e}^{-{x}^{2}}(2x^2-1)\right)

= 4 x 2 2 \displaystyle = 4{x}^{2}-2

Then, the concluding integral becomes

( 4 t 2 2 ) e ( 1 t ) 2 d t \displaystyle \int_{-\infty}^{\infty}{(4{t}^{2}-2){e}^{-{(1-t)}^{2}} dt}

whose computation will be the same as that of Hasan.

A general integral I n ( x ) {I}_{n}(x) can thus be computed similarly.

Kartik Sharma - 5 years, 10 months ago

Log in to reply

gud :) you did it nicely too

Aman Rajput - 5 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...